Conformational Dynamics in the Core of Human Y145Stop Prion Protein Amyloid Probed by Relaxation Dispersion NMR. Issue 2 (7th November 2018) - Shannon, Matthew D.; Theint, Theint; Mukhopadhyay, Dwaipayan; Surewicz, Krystyna; Surewicz, Witold K.; Marion, Dominique; Schanda, Paul; Jaroniec, Christopher P.
Abstract: Microsecond to millisecond timescale backbone dynamics of the amyloid core residues in Y145Stop human prion protein (PrP) fibrils were investigated by using 15 N rotating frame ( R 1ρ ) relaxation dispersion solid‐state nuclear magnetic resonance spectroscopy over a wide range of spin‐lock fields. Numerical simulations enabled the experimental relaxation dispersion profiles for most of the fibril core residues to be modelled by using a two‐state exchange process with a common exchange rate of 1000 s −1, corresponding to protein backbone motion on the timescale of 1 ms, and an excited‐state population of 2 %. We also found that the relaxation dispersion profiles for several amino acids positioned near the edges of the most structured regions of the amyloid core were better modelled by assuming somewhat higher excited‐state populations (∼5–15 %) and faster exchange rate constants, corresponding to protein backbone motions on the timescale of ∼100–300 μs. The slow backbone dynamics of the core residues were evaluated in the context of the structural model of human Y145Stop PrP amyloid. Abstract : Backbone dynamics in the core of Y145Stop human prion protein amyloid fibrils are investigated by using 15 N rotating frame relaxation dispersion solid‐state NMR. Protein backbone motions on timescales ranging from ∼0.1 to 1 ms and excited‐state conformer populations ranging from ∼2 to 15 % are detected for the different core residues and evaluated in the context of the structural model of Y145Stop human prion protein amyloid.